"Sometimes you have to take the person and show them how": adapting behavioral activation for peer recovery specialist-delivery to improve methadone treatment retention - Mary B. Kleinman; Morgan S. Anvari; Valerie D. Bradley; Julia W. Felton; Annabelle M. Belcher; C. J. Seitz-Brown; Aaron D. Greenblatt; Dwayne Dean; Melanie Bennett; Jessica F. Magidson (BMC, 2023)
Abstract Background Despite efficacy of medication for opioid use disorder, low-income, ethno-racial minoritized populations often experience poor opioid use disorder treatment outcomes. Peer recovery specialists, individuals with lived experience of substance use and recovery, are well-positioned to engage hard-to-reach patients in treatment for opioid use disorder. Traditionally, peer recovery specialists have focused on bridging to care rather than delivering interventions. This study builds on research in other low-resource contexts that has explored peer delivery of evidence-based interventions, such as behavioral activation, to expand access to care. Methods We sought feedback on the feasibility and acceptability of a peer recovery specialist-delivered behavioral activation intervention supporting retention in methadone treatment by increasing positive reinforcement. We recruited patients and staff at a community-based methadone treatment center and peer recovery specialist working across Baltimore City, Maryland, USA. Semi-structured interviews and focus groups inquired about the feasibility and acceptability of behavioral activation, recommendations for adaptation, and acceptability of working with a peer alongside methadone treatment. Results Participants (N = 32) shared that peer recovery specialist-delivered behavioral activation could be feasible and acceptable with adaptations. They described common challenges associated with unstructured time, for which behavioral activation could be particularly relevant. Participants provided examples of how a peer-delivered intervention could fit well in the context of methadone treatment, emphasizing the importance of flexibility and specific peer qualities. Conclusions Improving medication for opioid use disorder outcomes is a national priority that must be met with cost-effective, sustainable strategies to support individuals in treatment. Findings will guide adaptation of a peer recovery specialist-delivered behavioral activation intervention to improve methadone treatment retention for underserved, ethno-racial minoritized individuals living with opioid use disorder.